Preorganizing linear (self-complementary) quadruple hydrogen-bonding arrays using intramolecular hydrogen bonding as the sole force - Prabhakaran, Panchami; Puranik, Vedavati G.; Sanjayan, Gangadhar J. (Journal of Organic Chemistry, 2005)
In this article we describe a rational approach for prefixing multiple cooperative binding sites in an ideal spatial arrangement on a structurally rigid backbone, constrained exclusively by intramolecular hydrogen bonding. The idea is exemplified by the ability of the self-assembling constructs la-e and 2a,b to form hydrogen-bonded dimers, whose structural preorganization has been solely effected by intramolecular hydrogen bonding. The readily accessible amidinourea backbone has been used as a common platform for the construction of a variety of such self-assembling systems. ESI mass spectrometry and single-crystal X-ray diffraction studies have been particularly effective in investigating the self-assembling propensities of these systems. Remarkably, most the H-bonded dimers reported herein undergo an unusual mode of self-assembly, using intermolecular four-membered ring hydrogen-bonded interaction, affording extended supramolecular networks.

N,N `,N `'-Tri-Boc-guanidine (TBG): a common starting material for both N-alkyl guanidines and amidinoureas - Prabhakaran, Panchami; Sanjayan, Gangadhar J. (Tetrahedron Letter, 2007)
{In this Letter, we describe the unexpected reaction pattern of N,N',N''
Keywords: 1-substituted-1H-1; 2; 3; 4-tetrazoles; Ionic liquid; sodium azide; substituted amine; triethyl orthoformate

Sequence-specific unusual (1 -> 2)-type helical turns in alpha/beta-hybrid peptides - Prabhakaran, Panchami; Kale, Sangram S.; Puranik, Vedavati G.; Rajamohanan, P. R.; Chetina, Olga; Howard, Judith A. K.; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Journal of the American Chemical Society, 2008)
This article describes novel conformationally ordered (alpha/beta-hybrid peptides consisting of repeating L-proline-anthranilic acid building blocks. These oligomers adopt a compact, right-handed helical architecture determined by the intrinsic conformational preferences of the individual amino acid residues. The striking feature of these oligomers is their ability to display an unusual periodic pseudo beta-turn network of nine-membered hydrogen-bonded rings formed in the forward direction of the sequence by 1–>2 amino acid interactions both in solid-state and in solution. Conformational investigations of several of these oligomers by single-crystal X-ray diffraction, solution-state NMR, and ab initio MO theory suggest that the characteristic steric and dihedral angle restraints exerted by proline are essential for stabilizing the unusual pseudo beta-turn network found in these oligomers. Replacing proline by the conformationally flexible analogue alanine (Ala) or by the conformationally more constrained alpha-amino isobutyric acid (Aib) had an adverse effect on the stabilization of this structural architecture. These findings increase the potential to design novel secondary structure elements profiting from the steric and dihedral angle constraints of the amino acid constituents and help to augment the conformational space available for synthetic oligomer design with diverse backbone structures.

Novel foldamer structural architecture from cofacial aromatic building blocks - Prabhakaran, Panchami; Puranik, Vedavati G.; Chandran, Jima N.; Rajamohanan, Pattuparampil R.; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Chemical Communications, 2009)
This communication demonstrates the utility of peri-substituted 1,8-diphenylnaphthalene as an effective building block for the construction of novel conformationally ordered synthetic oligomers displaying cofacial structural features.

Sterically controlled naphthalene homo-oligoamides with novel structural architectures - Prabhakaran, Panchami; Puranik, Vedavati G.; Chandran, Jima N.; Rajamohanan, P. R.; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2009)
Herein we report novel naphthalene homo-oligoamides, derived from 4-amino-3-methoxy-naphthalene-2-carboxylic acid and 4-amino-1-methoxy-naphthalene-2-carboxylic acid as monomer building blocks, that display an anti-periplanar arrangement of the naphthyl rings, primarily induced by steric interactions between adjacent groups and functionalities.

1,8-Bis(4-methoxy-3-nitrophenyl)naphthalene - Prabhakaran, Panchami; Puranik, Vedavati G.; Sanjayan, Gangadhar J. (Acta Crystallographica Section E-Structure Reports Online, 2011)
Molecules of the title compound, C(24)H(18)N(2)O(6), are located on a twofold rotation axis passing through through the central C-C bond of the naphthalene ring system. The molecular conformation is characterized by a roughly coplanar arrangement of the two substituted phenyl rings [dihedral angle 18.53 (5)degrees]. These two aryl rings are each twisted by 65.40 (5)degrees from the plane of the naphthyl unit.

Conformationally rigid aromatic amino acids as potential building blocks for abiotic foldamers - Ramesh, Veera V. E.; Roy, Arup; Vijayadas, Kuruppanthara N.; Kendhale, Amol M.; Prabhakaran, Panchami; Gonnade, Rajesh G.; Puranik, Vedavati G.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2011)
This communication describes the development of conformationally constrained unnatural aromatic amino acids, constructed on rigid backbone wherein the carboxyl and amino groups project in two dimensions (planes) on the aromatic framework. Such a feature offers the possibility of design and development of conformationally ordered synthetic oligomers with intriguing structural architectures distinct from those classically observed. Furthermore, such amino acids will have the potential to extend the conformational space available for foldamer design with diverse backbone conformation and structural architectures.

Diversifying the structural architecture of synthetic oligomers: the hetero foldamer approach - Roy, Arup; Prabhakaran, Panchami; Baruah, Pranjal Kumar; Sanjayan, Gangadhar J. (Chemical Communications, 2011)
Conformationally ordered synthetic oligomers, also called ``foldamers'', have attracted considerable attention in recent years owing to their ability to mimic the structural architecture of biopolymers and also because of their potential applications in biomedical and material science fields. Until recently, the major focus in this area has been the development of oligomers featuring a single type of monomer building blocks. However, due to the enormous possibility of augmenting the conformational space available for oligomer design, the hetero foldamer approach has been introduced very recently. This feature article aims to describe foldamers with unique structural architectures, exclusively featuring heterogeneous backbones (hetero foldamers).

Foldamers: they're not just for biomedical applications anymore - Prabhakaran, Panchami; Priya, Gowri; Sanjayan, Gangadhar J. (Angewandte Chemie-International Edition, 2012)
Keywords: Foldamers; foldaxanes; molecular shuttles; nanotechnology

Ant-pro reverse-turn motif. structural features and conformational characteristics - Thorat, Vijaykumar H.; Ingole, Tukaram S.; Vijayadas, Kuruppanthara N.; Nair, Roshna V.; Kale, Sangram S.; Ramesh, Veera V. E.; Davis, Hilda C.; Prabhakaran, Panchami; Gonnade, Rajesh G.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; et al. (European Journal of Organic Chemistry, 2013)
This article details the characteristic conformational features of the Ant-Pro reverse turn ? a folded pseudo -turn motif that displays a closed nine-membered-ring hydrogen-bonded network involving just two amino acid residues, namely anthranilic acid (Ant; a constrained -amino acid), and proline (Pro; a constrained -amino acid). The results from the extensive investigation of ten crystal structures and their NMR conformations in the solution state provide a clear idea about the conformational characteristics of the Ant-Pro reverse turn. The Ant and Pro residues, which form the turn segment, maintain a perfect antiperiplanar orientation throughout, leaving little possibility for the formation of the otherwise possible six-membered hydrogen-bonding that requires a coplanar disposition of the two amino acid residues, as clearly evident from investigation of several crystal structures. The closed hydrogen-bonded network observed in the Ant-Pro reverse turn motif, formed in the forward direction of the sequence (12 amino acid interactions) involving only two amino acid residues, is in stark contrast to the native -turns that involve four residues to form hydrogen-bonded network featuring backward 14 amino acid interactions. The readily available two-residue Ant-Pro motif raises the possibility of a practical utility, particularly in the application of rigidifying flexible peptide backbones by inserting the robust Ant-Pro reverse turn motifs into their backbone.
Keywords: Peptides; Peptidomimetics; Protein folding; Protein structures

Ester vs. amide on folding: a case study with a 2-residue synthetic peptide - Vijayadas, Kuruppanthara N.; Nair, Roshna V.; Gawade, Rupesh L.; Kotmale, Amol S.; Prabhakaran, Panchami; Gonnade, Rajesh G.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2013)
Although known for their inferiority as hydrogen-bonding acceptors when compared to amides, esters are often found at the C-terminus of peptides and synthetic oligomers (foldamers), presumably due to the synthetic readiness with which they are obtained using protected peptide coupling, deploying amino acid esters at the C-terminus. When the H-bonding interactions deviate from regularity at the termini, peptide chains tend to ``fray apart''. However, the individual contributions of C-terminal esters in causing peptide chain end-fraying goes often unnoticed, particularly due to diverse competing effects emanating from large peptide chains. Herein, we describe a striking case of a comparison of the individual contributions of C-terminal ester vs. amide carbonyl as a H-bonding acceptor in the folding of a peptide. A simple two-residue peptide fold has been used as a testing case to demonstrate that amide carbonyl is far superior to ester carbonyl in promoting peptide folding, alienating end-fraying. This finding would have a bearing on the fundamental understanding of the individual contributions of stabilizing/destabilizing non-covalent interactions in peptide folding.